A Laser Damage Threshold for Microscope Glass Slides - Tuzun, Pervin; Kadi, Omer Faruk; Yildiz, Fikret; Hamid, Ramiz; Nasibov, Humbat (Mdpi, 2023)
Laser-based light sources have fostered innovative developments in biomedical and biosensor fields. However, laser-induced damage to optical components is a limitation for designing and implementing highly sensitive biosensors, necessitating the development and characterization of suitable optical components. Microscope glass slides are among the most extensively used optical units in this field. This study investigated the laser-induced damage threshold (LIDT) of high-quality microscope glass slides obtained from three different vendors. An S-on-1 protocol following the ISO 21254 series standards was adopted to ensure a meaningful comparative analysis. Multiple laser pulses at a constant fluence (at the three laser wavelengths most widely used in biosensors) were used for LIDT tests. An automated test bench was developed and employed to minimize the influence of human factors on the test results. The fatigue damage mechanism was observed in all the samples. The findings revealed good consistency among LIDT values within and across batches from the same vendor. However, a notable discrepancy was observed when comparing the results of slides obtained from different vendors, with threshold values differing by up to two-fold. This study emphasizes the need to carefully consider the glass material source when selecting microscope glass slides for laser-sensitive applications.
Keywords: laser-induced damage threshold; LIDT; fluence; microscope glass slides; characteristic curve; damage probability; ISO 21254 standards; S-on-1